Edukasi, Pelatihan Evidence-Based Practice In Nursing, dan Evaluasi Pelaksanaan 7 (Tujuh) Benar Pemberian Obat - Sri Rahayu; Melati Fajarini (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
ABSTRACT Nursing practice based on scientific evidence or commonly known as Evidence-Based Practice in Nursing is still an interesting trend and issue in Indonesia. This is still something new for nurses because almost the majority of nursing practice based on hospital Standard Operational Procedure (SOP). In fact, the SOP is not all of nursing practice based on scientific evidence. One of the practice of nursing is medication administration which is need to collaboration with the doctor. Therefore, it is necessary to evaluate the administration of 7 (seven) rights of medication. The expected output target is to increase knowledge, and understanding of evidence based practice in nursing in the administration of 7 (seven) rights of medication. The method used education, training, and evaluation of the implementation of 7 rights of medication. The results showed that the majority of nurses had knowledge of 7 rights of medication were 63.3%, and evaluation by direct observations about the implementation of 7 rights of medication were between 50-100%. Furthermore, nurses are expected to be able to evaluate independently and continuously by using the same minimum method or developing it to get accurate data.